On the Bus - Adam Guillain (UK Rising Stars Uk Ltd, 2016)
Comet Street Kids reading books follow the adventures of Rav, Asha, Tess and Finn, four of the residents of Comet Street. There are 72 exciting stories in the series that children won't be able to put down. Rav's dad is taking Rav and his friends on the bus. Rav loves staring out of the window to see what goes past, but he'd be better be careful not to get left behind! Reading 4-5 years
Keywords: ( Independent Reading ) -- ( Independent Reading )